Patterns of Safety Incidents in a Neonatal Intensive Care Unit - Brado, Luise; Tippmann, Susanne; Schreiner, Daniel; Scherer, Jonas; Plaschka, Dorothea; Mildenberger, Eva; Kidszun, André (Frontiers in Pediatrics, 2021)
Introduction: Safety incidents preceding manifest adverse events are barely evaluated in neonatal intensive care units (NICUs). This study aimed at identifying frequency and patterns of safety incidents in our NICU. Methods: A 6-month prospective clinical study was performed from May to October 2019 in a German 10-bed level III NICU. A voluntary, anonymous reporting system was introduced, and all neonatal team members were invited to complete paper-based questionnaires following each particular safety incident. Safety incidents were defined as safety-related events that were considered by the reporting team member as a “threat to the patient's well-being” which “should ideally not occur again.” Results: In total, 198 safety incidents were analyzed. With 179 patients admitted, the incident/admission ratio was 1.11. Medication errors (n = 94, 47%) and equipment problems (n = 54, 27%) were most commonly reported. Diagnostic errors (n = 19, 10%), communication problems (n = 12, 6%), errors in documentation (n = 9, 5%) and hygiene problems (n = 10, 5%) were less frequent. Most safety incidents were noticed after 4–12 (n = 52, 26%) and 12–24 h (n = 47, 24%), respectively. Actual harm to the patient was reported in 17 cases (9%) but no life-threatening or serious events occurred. Of all safety incidents, 184 (93%) were considered to have been preventable or likely preventable. Suggestions for improvement were made in 132 cases (67%). Most often, implementation of computer-assisted tools and processes were proposed. Conclusion: This study confirms the occurrence of various safety incidents in the NICU. To improve quality of care, a graduated approach tailored to the specific problems appears to be prudent.